Inclusive business models for access to quality fish seed and technical assistance: Insights from Ghana - Kruijssen, Froukje; Rappoldt, Anne; Ragasa, Catherine; Newton, Julie; Agyakwah, Seth K.; Asmah, Ruby; Mensah, Emmanuel Tetteh-Doku; Justus Teye; Amewu, Sena (International Food Policy Research Institute, 2020)
Over the past decade, Ghana’s tilapia farming has experienced tremendous growth in production; however, much of the growth has been driven by large-scale cage farmers around Lake Volta. It remains unclear how this growth is and can be made more inclusive of poor and young women and men. This study was conducted to analyze different inclusive business models along the fish seed value chain that can potentially be implemented in Ghana. Based on literature review, field interviews, analysis of survey data, and stakeholder workshops, this study develops four business model prototypes for seed multiplication and distribution to increase farmers’ access to and use of quality tilapia seed: (1) Nursery , which buy fish fry from a reliable hatchery, transport them to locations near other farmers, and grow it to a larger size; (2) Local feed mill, with pelleting machine and technical knowledge to advise on feed formulation; (3) Agents, technical experts who supply fingerlings, handle transport and marketing, and provide technical advice; and (4) Local hatchery, which obtains brood stock from a reliable source, produces local fingerlings to sell to nearby farmers, and provides technical support. Initial ex ante financial and profitability analyses were undertaken and will be refined according to the actual context in the particular district where the sensitization and pilot-testing will take place. These business models have the potential not only to increase farmers’ access to and use of quality tilapia seed but also to provide livelihood and income generation along the fish seed value chain.